(untitled) (Journal of Enam Medical College, 2014)
Pure primary ovarian choriocarcinoma is an extremely rare and aggressive tumor. It can be of gestational or nongestational in origin. The gestational type can arise from an ovarian pregnancy or can be of metastatic origin from uterine choriocarcinoma. The nongestational type is a very rare germ cell neoplasm. It is important to distinguish between two types of choriocarcinomas as nongestational origin is highly malignant and has worse prognosis than gestational type. But it is very difficult to differentiate by routine histological examination. Nongestational choriocarcinoma has been found to be resistant to single agent chemotherapy. It occurs usually around 13 years of age and is mainly confined to females under 20. Here we report a case of primary pure nongestational choriocarcinoma of the ovary in an unmarried girl of 14 years, diagnosed in 2001 and treated successfully with surgery and combination chemotherapy and remained disease-free till last reporting in September 2013. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18070 J Enam Med Col 2014; 4(1): 56-59